Age, Experience and Language and Literacy Skills in English-Arabic Speaking Syrian Refugees - Alexandra Gottardo; Redab Al-Janaideh; Johanne Paradis; Adriana Soto-Corominas; Xi Chen; Norah Amin (Languages, 2023)
Although age of acquisition (AoA) is frequently used when examining the endpoint of second language (L2) learning, it is rarely used to examine the initial phases of L2 acquisition. The present study provided a unique look at the role of AoA in early language and literacy acquisition in the L2 by a priori selecting two groups of Arabic-English speakers based on their ages, 6–8-year-olds (N = 43) and 9–13-year-olds (N = 53). These Syrian refugees were matched on English experience, having immigrated to Canada and having learned English for two years or less. Raw scores on language and literacy measures were compared across groups. The older group had higher scores on all first language (L1) variables. The groups did not differ on most L2 variables except for English word reading. Additionally, L1 and L2 variables were examined in relation to English word and pseudoword reading with different patterns of relations found for the two groups. For the younger group, phonological awareness and vocabulary were related to reading, while for the older group phonological awareness and morphological awareness were key predictors. These finding points to the unique relations among age, age of acquisition, L1 skills, and L2 language and literacy skills.